PENATAAN LAHAN PERTANIAN BERKELANJUTAN PADA LERENG GUNUNG MARAPI TANAH DATAR PROVINSI SUMATERA BARAT - Eri Barlian; Iswandi Umar (Universitas Negeri Padang, 2020)
Land use for agriculture has increased every year. As a result of the increased need for agricultural land causing degradation of agricultural land. The purpose of this study was to conduct structured directives for agricultural land use. To determine the direction of structuring the use of agricultural land using a geographic information system approach. The indicator used in determining the arrangement of sustainable agricultural land use is; slope, soil type, rainfall, geology, and land use. Furthermore, to determine the direction of policy on the use of agricultural land using the ISM approach. The results of the land structuring analysis of the slopes of Mount Marapi show that around 35 percent of agricultural land cannot be utilized for cultivation areas. Actual conditions, around 20 percent of the area has been used for farm land. herefore, as a policy direction for sustainable land use the government must conduct land use counseling in accordance with the carrying capacity of the land.